RANCANG-BANGUN KETELPASTEURISASIDAN PENDINGINAN SUSU SEGAR - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A milk pasteurizer for home industry with the capacity of 20 litres has been designed and constructed in this program. The milk pasteurizer test that was conducted in UPP Wargamulya indicated that the time required for pasteurizing 20 litres of milk was 2 hours. It consisted of 60 minutes heating, 40 minutes cooling, and 20 minutes preparation. The operational cost was Rp. 6.8So,00/batch or equal to Rp. 3.42,5 /litre of pasteurized milk.